The Role of Sanad Studies in Ensuring the Authenticity of Mu'allaq Balaghât Hadiths in the Book of Muwatta' Malik - Hafizzullah; Sepri Aulia; Dewi Putri (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2023)
One of the separate studies in hadith scholarship is Imam Malik's narration model using sighat tahammul which is different from other scholars. That is with the hadiths balâghât (hadiths beginning with "بلغني" or "أنه بلغه" In the study of sanad in general, the hadith belongs to the category of munqathi' (sanad interrupted. This study focuses on the hadiths of Balaghât Muwattha' which are categorized as mu'allaq (dependent), by using the method of takhrîj hadith with the approach of I'tibâr, which examines the existence of other hadiths al-kutub at-tis'ah that support the narration of Imam Malik. From research it can be concluded, that the hadith balâghât mu'allaq in Kitab al-Muwaththa' has a muttashil supporting history from other hadith books, especially al-kutub at-tis'ah, so that with the existence of other muttashil narrations, making the hadith balâghât mu'allaq Malik can be used as a hujjah.